An Effort to Increase Zakat Awareness: The Role of Public Figures - Zaenal, Muhammad Hasbi; Susianti, Meis Winih; Ikhwan, Ihsanul; Adiningshih, Siti Maulida (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2024)
This research aims to analyze the influence of public figures on the intention to pay zakat. The variables adopted in this research are variables related to the characteristics of public figures: trustworthiness, attractiveness, and expertise. This study succeeded in collecting primary data from 216 respondents which were then analyzed using the Structural Equation Modeling (SEM) method. This research shows that the variables trustworthiness, attractiveness, and expertise positively and significantly influence the intention to pay zakat. Based on the results, zakat institutions are expected to select reliable public figures who can be trusted by the community, have an appeal to the community, and have a good understanding and competence about zakat.Abstrak:Penelitian ini bertujuan untuk menganalisis pengaruh public figures terhadap intensi membayar zakat. Variabel yang diadopsi dalam penelitian ini merupakan variabel yang terkait dengan karakteristik public figures yakni variabel trustworthiness, attractiveness, dan expertise. Studi ini berhasil mengumpulkan data primer dari 216 responden yang selanjutnya dianalisis dengan menggunakan metode Structural Equation Modeling (SEM). Hasil penelitian ini menunjukkan bahwa variabel trustworthiness, attractiveness, dan expertise secara positif signifikan memengaruhi intensi membayar zakat. Berdasarkan hasil penelitian ini, badan/lembaga zakat diharapkan dapat memilih public figures yang dapat diandalkan serta dapat dipercaya oleh masyarakat, memiliki daya tarik bagi masyarakat, serta memiliki pemahaman dan kompetensi yang baik tentang zakat.